KONFLIK KOMUNIKASI DALAM PROSES REFUND DAN RETUR BARANG DI SHOPEE: TINJAUAN KOMUNIKASI DAN NEGOSIASI BISNIS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze communication problems and business negotiation processes in the refund and return of goods on the Shopee marketplace platform. Using a qualitative approach through library research, this study examines various scientific journal sources related to business communication, communication barriers, business negotiation, and consumer protection in online transactions. The results show that communication barriers—such as slow customer service responses, automated reply systems, and lack of information transparency—significantly affect negotiation quality and consumer satisfaction. Consumer bargaining positions tend to be weak as they are entirely dependent on platform policies. This study concludes that improving business communication effectiveness is a fundamental factor in creating a fair negotiation process and increasing consumer trust in digital platforms.